PENGARUH VARIASI PENAMBAHAN AIR DAN SEMEN PADA SUATU PERENCANAAN CAMPURAN (MIX DESIGN) TERHADAP SUSUT BETON DAN KUAT TARIK BELAH BETON (SUATU PENELITIAN BETON DENGAN FAS 0,3, 0,4 DAN 0,5) - Teuku Budi Aulia; Muhammad Ali Akoeb (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Note that the addition of cement in mixing concrete will increase the strength of concrete when water is added only if the concrete strength will be decreased but increased workabilitas concrete . This study aims to determine the effect of the addition of water and cement for concrete and tensile strength dropped concrete sides . Test substance used for testing concrete and tensile strength decreased Shopping concrete cylinder diameter is 15 cm; 30 cm high by 72 . Cement Water Factor (FAS ) used are 0.3 , 0.4 and 0.5 . In this research is the addition of water and cement 0 % , 10 % , 20 % and 30 % respectively for the FAS. Where for every percentage increase in water and cement made 6 test objects . Testing is done in the space fell sheltered by looking at the results of curtailment reading on the dial gauge test objects . Shop tensile strength testing done at 28 days , with an increase of 1 ton each . Stretching things a test read tranducer tool mounted on the frame gauge connected to a data logger tool . The results showed that the decreased stretch of concrete increases with the increase in the percentage of water and cement penambahaan done , while for increased tensile strength of the concrete sides of the optimum place on the addition of water and cement by 20 % for each of his FAS . The analysis of variance showed that there was significant influence between the percent increase in water and cement to the sides of the concrete tensile strength .